Pengaruh Penggunaan Media Pembelajaran PAI Berbasis Aplikasi Educaplay terhadap Hasil Belajar Siswa di SMP Negeri 2 Ranah Batahan - Sherly Herlianti; Jasmienti Jasmienti (YASIN, 2026)
The use of digital learning media in Islamic Religious Education (PAI) has received attention in various previous studies; however, studies that specifically discuss the effect of Educaplay application-based PAI learning media on the learning outcomes of Grade VII students at SMP Negeri 2 Ranah Batahan remain limited. This study aims to analyze the effect of using Educaplay application-based PAI learning media on students’ learning outcomes. This study used a quantitative approach with a quasi-experimental design through a Posttest Only Control Group Design. The research sample involved 56 students selected using a purposive sampling technique, consisting of 28 students in the experimental class and 28 students in the control class. Data were collected using an objective learning outcomes test instrument that had undergone validity and reliability testing, then analyzed using inferential statistics through normality testing, homogeneity testing, and an Independent Sample t-Test with the assistance of SPSS version 20. The results show that the average learning outcome score of the experimental class was 77.9286, which was higher than that of the control class at 67.7857. The hypothesis testing results show that the calculated t-value of 4.087 was greater than the critical t-value of 2.005, with a significance value of 0.000 < 0.05, indicating a significant effect of using the Educaplay application on students’ learning outcomes. These findings contribute to strengthening constructivist theory and the Cognitive Theory of Multimedia Learning and broaden understanding of the effectiveness of digital learning media in PAI. The conclusion of the study affirms that the use of the Educaplay application plays an important role in improving students’ learning outcomes through more interactive, engaging, and technology-based learning. The implications of this study provide practical contributions for teachers and schools in optimizing the use of digital learning media to improve the quality of PAI learning.